Highly sensitive GaAs/AlGaAs heterojunction bolometer - Pitigala, P.K.D.D.P.; Jayaweera, P.V.V.; Matsik, S.G.; Perera, A.G.U.; Liu, H.C. (Sensors and actuators. A. Physical., 2011)
GaAs/AlGaAs multilayer heterojunction structures with different aluminum (Al) fractions and emitter doping densities were tested to identify optimum parameters for high temperature coefficient of resistance (TCR). Higher Al fractions and lower doping densities showed higher TCR. Additionally, p-doped heterojunction structures showed a higher TCR compared to an n-doped one with similar parameters. A p-doped multilayer superlattice heterojunction structure with 30 periods of GaAs/Al 0.57Ga 0.43As junctions, operating at room temperature showed a TCR of ∼4% and bolometer like infrared (IR) response up to 20 μm with a D* of 1.7 × 10 6 Jones. This TCR is higher than that of VO x or α-Si bolometers. At low temperatures (50 K) some of these devices have shown TCR values of over 30%.